Daniel Frederik Eschricht (1798-1863) Peter Wilhelm Lund (1801-1880) : Danish pioneers in experimental physiology ; Historians, philosophers and practitioners on Claude Bernard’s : introduction à l’étude de la médecine expérimentale. - Jørgensen, C. Barker. (Copenhagen)
44 s.